2023
DOI: 10.1038/s41380-023-02290-x
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-mediated upregulation of HCN channels in VTA dopamine neurons promotes cocaine reinforcement

Lianwei Mu,
Xiaojie Liu,
Hao Yu
et al.

Abstract: Chronic cocaine exposure induces enduring neuroadaptations that facilitate motivated drug taking. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are known to modulate neuronal firing and pacemaker activity in ventral tegmental area (VTA) dopamine neurons. However, it remained unknown whether cocaine self-administration affects HCN channel function and whether HCN channel activity modulates motivated drug taking. We report that rat VTA dopamine neurons predominantly express Hcn3-4 mRNA, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…We found some overlap in the differentially expressed genes within the two dopamine neuron populations, including concordant up‐regulation potassium channel Hcn1 , and cAMP binding protein Creb5 . These targets are of particular interest as chronic opioids are known to disrupt expression of potassium channels, 11 and cAMP‐mediated upregulation of HCNs in dopamine neurons was recently shown to promote cocaine self‐administration 44 . We also found enrichment for Pi3k‐Akt signalling pathway genes in the combinatorial neurons and our selected GABA neurons cluster.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We found some overlap in the differentially expressed genes within the two dopamine neuron populations, including concordant up‐regulation potassium channel Hcn1 , and cAMP binding protein Creb5 . These targets are of particular interest as chronic opioids are known to disrupt expression of potassium channels, 11 and cAMP‐mediated upregulation of HCNs in dopamine neurons was recently shown to promote cocaine self‐administration 44 . We also found enrichment for Pi3k‐Akt signalling pathway genes in the combinatorial neurons and our selected GABA neurons cluster.…”
Section: Discussionmentioning
confidence: 52%
“…These targets are of particular interest as chronic opioids are known to disrupt expression of potassium channels, 11 and cAMP‐mediated upregulation of HCNs in dopamine neurons was recently shown to promote cocaine self‐administration. 44 We also found enrichment for Pi3k‐Akt signalling pathway genes in the combinatorial neurons and our selected GABA neurons cluster. This included upregulation of neurotrophic factors Ngf and Gdnf .…”
Section: Discussionmentioning
confidence: 56%
“… 68 Interestingly, recent studies have demonstrated contrasting modulatory effects of chronically altered cAMP on HCN channels activity in pyramidal neurons from dorsal hippocampal and dopamine neurons from VTA. 64 , 69 Therefore, investigating whether cAMP or TRIP8b participates in the HCN channelopathy of the LHb under the comorbidity of SNI‐induced chronic pain and major depression and elucidating their interactions with HCN channels are important areas for future research aimed at elucidating the central mechanisms underlying the pathogenesis of CADS in chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…We found some overlap in the differentially expressed genes within the two dopamine neuron populations, including concordant up-regulation potassium channel Hcn1 , and cAMP binding protein Creb5. These targets are of particular interest as chronic opioids are known to disrupt expression of potassium channels 12 , and cAMP-mediated upregulation of HCNs in dopamine neurons was recently shown to promote cocaine self-administration 44 . We also found enrichment for Pi3k-Akt signaling pathway genes in the combinatorial neurons and our selected GABA neurons cluster.…”
Section: Discussionmentioning
confidence: 99%
“…These targets are of particular interest as chronic opioids are known to disrupt expression of potassium channels 12 , and cAMP-mediated upregulation of HCNs in dopamine neurons was recently shown to promote cocaine selfadministration 44 . We also found enrichment for Pi3k-Akt signaling pathway genes in the combinatorial neurons and our selected GABA neurons cluster.…”
Section: Discussionmentioning
confidence: 99%